[A01] Fractured Proximal Nitinol Ring in Fenestrated Anaconda Device: A Multicentre Case Series. (November 2022) - El-Sayed, Tamer; Zahed, Asef; McCaslin, James; Williams, Robin; Bungay, Peter; Nandhra, Sandip
Abstract : Objective: There has been an increase in the number and complexity of aortic aneurysms treated by fenestrated endovascular stent grafts. The Terumo Aortic Anaconda endovascular aortic stent graft system has been used since 2010 and is one of two widely used platforms. A multicentre case series of Anaconda Stent Graft with proximal ring fractures is reported. Methods: This was a multicentre retrospective case series of proximal ring fractures in patients who underwent fenestrated endovascular aortic aneurysm repair (FEVAR) with the Anaconda stent graft between 2010 and 2021 in two UK tertiary vascular centres (the Freeman Hospital, Newcastle, and the Royal Derby Hospital, Derby). Results: Fifteen patients (median age 68 years; range 64 – 88) out of 253 patients who underwent FEVAR with the Anaconda stent graft system were found to have incidental fractures of the proximal sealing ring on routine surveillance between 23 March 2013 and 12 November 2021. Four cases showed wire fracture from the proximal sealing ring and migration to the surrounding tissue/organs. One patient developed aneurysm sac expansion with type IA due to stent migration and subsequently one fenestration occlusion required secondary intervention. Other patients (14 out of 15) did not show stent migration or loss of the proximal sealing zone and were managed conservatively with no clinical harm identified to date. Conclusion: Early data in this case series highlight the importance of surveillance following aortic endograft placement. A wider review across additional centres is required to understand the clinical consequences of stent ring fracture and any adverse anatomical prognostic features.